2015
DOI: 10.1371/journal.pone.0143575
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nicotine Exposure In Vivo and In Vitro Inhibits Vitamin B1 (Thiamin) Uptake by Pancreatic Acinar Cells

Abstract: Thiamin (vitamin B1), a member of the water-soluble family of vitamins, is essential for normal cellular functions; its deficiency results in oxidative stress and mitochondrial dysfunction. Pancreatic acinar cells (PAC) obtain thiamin from the circulation using a specific carrier-mediated process mediated by both thiamin transporters -1 and -2 (THTR-1 and THTR-2; encoded by the SLC19A2 and SLC19A3 genes, respectively). The aim of the current study was to examine the effect of chronic exposure of mouse PAC in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
2
15
0
1
Order By: Relevance
“…Human primary pancreatic acinar cells (hPAC) were isolated from cadaveric pancreatic tissues of organ donors at Islet Cell Laboratory at the University of Louisville (Louisville, KY), and at City of Hope (Duarte, CA). Briefly, after informed consent had been obtained, pancreata of subjects (25-to 65-yr-old males) were removed from the donors and digested to separate islets from ductal-acinar trees and purified as described previously (36). The resulting acini were transported to the University of California, Irvine (Ͻ48 h after isolation) and cultured in Ham's F-12K growth medium supplemented with the following: 10% FCS, 5% BSA, 10 ng/ml epidermal growth factor, and 0.1 mg/ml soybean trypsin inhibitor, as described by us and others before (31,36).…”
Section: Flagellin Exposure Of Human Pacs and Uptake Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human primary pancreatic acinar cells (hPAC) were isolated from cadaveric pancreatic tissues of organ donors at Islet Cell Laboratory at the University of Louisville (Louisville, KY), and at City of Hope (Duarte, CA). Briefly, after informed consent had been obtained, pancreata of subjects (25-to 65-yr-old males) were removed from the donors and digested to separate islets from ductal-acinar trees and purified as described previously (36). The resulting acini were transported to the University of California, Irvine (Ͻ48 h after isolation) and cultured in Ham's F-12K growth medium supplemented with the following: 10% FCS, 5% BSA, 10 ng/ml epidermal growth factor, and 0.1 mg/ml soybean trypsin inhibitor, as described by us and others before (31,36).…”
Section: Flagellin Exposure Of Human Pacs and Uptake Studiesmentioning
confidence: 99%
“…Using a variety of physiological, cellular, and molecular approaches (including appropriate knockout and knockdown approaches), we have previously shown that thiamin uptake by mouse and human pancreatic acinar cells is via a specific carrier-mediated process and involves thiamin transporters 1 and 2 (THTR-1 and THTR-2) (38,39). Other studies from our laboratory have examined the effect of chronic exposure of PACS to alcohol and to specific components of cigarette smoke on thiamin uptake and have delineated the cellular/molecular mechanisms involved in the identified effects (34,35,36,39).…”
Section: Introductionmentioning
confidence: 99%
“…In that context, using chemical inhibitors and mice with genetic deletions, several studies have found that pancreatitis effects of NNK (with acinar cells and in vivo) appear to be mediated by an α-7-nicotinic receptor 37 . A very recent study suggested that one action of NNK in the pancreas was to reduce the activity of plasma-membrane and mitochondrial thiamine transporters 38, 39. This NNK effect was linked to reduced cellular mitochondrial function and adenosine triphosphate depletion.…”
Section: Animal Models Of Clinical Acute Pancreatitismentioning
confidence: 99%
“…Another possible downstream pathway that has been investigated is thiamine (vitamin B 1 ) uptake by pancreatic acinar cells [ 42 44 ]. NKK has been shown to inhibit thiamine uptake in pancreatic acinar cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%